Pengaruh Corporate Social Responsibility Terhadap Kepuasan Nasabah Sektor Perbankan - Kristiana Greta Calosa; Marcella Aullia Jayadi; Hwihanus (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This study investigates the relationship between customer loyalty and happiness across various banking sectors and corporate social responsibility, or CSR. This report integrates findings from various studies conducted in various regions, including Indonesia, Pakistan, Saudi Arabia and Peru. Research consistently shows that Corporate Social Responsibility (CSR) activities have a positive effect on the company's image which ultimately increases customer satisfaction and loyalty. Specifically, this study uses different methodologies, such as path analysis, Structural Equation Modeling (SEM), and Pearson Correlation Coefficient, to analyze data from various sample sizes. In Indonesia, the impact of Corporate Social Responsibility (CSR) on company image and customer satisfaction was highlighted using a sample of 100 customers. Something similar also happened in Pakistan, a study involving 219 trusted respondents found that Corporate Social Responsibility (CSR) significantly increased customer satisfaction and loyalty, with corporate image acting as a strong moderating factor. In Saudi Arabia, an analysis of 624 banking customers revealed that Corporate Social Responsibility (CSR) activities have a strong positive influence on customer satisfaction and loyalty. Research in Peru further supports these findings, showing that Corporate Social Responsibility (CSR), mediated by customer trust, significantly increases customer loyalty, with the model explaining 63.6% of customer loyalty. These studies underscore the strategic importance of Corporate Social Responsibility (CSR) in cultivating a positive corporate image and increasing customer satisfaction, offering valuable insights for bank managers and directors in developing effective Corporate Social Responsibility (CSR) strategies.